The Face of the Qur'an in Media: An Exploration of Quranic Verses in Rubric "Hikmah" of Republika Daily Newspaper: [Wajah Al-Qur’an dalam Media: Penelusuran Ayat-Ayat al-Qur’an dalam Rubrik Hikmah Harian Umum Republika] - Ahmad Suhendra (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2014)
This article will discuss the verses of the Qur'an, specifically appeared in the Republika Newspaper Rubric of “Hikmah”. The articles include only eight randomly selected ones in March 2014. The analysis deals with what kind of values discussed in the media related to al-Qur'an. The results showed that though there were attempts to inform the teachings or the values contained in the religion through the media, but it is still within a narrow range. The analysis shows that indeed the content of “Hikmah” rubric is more oriented on the religious motivations than philosophical one.[Artikel ini akan menelusuri ayat-ayat al-Qur’an Koran Repbulika, khususnya Rubrik Hikmah. Tulisan yang dikaji dipilih hanya delapan secara acak selam bulan Maret 2014. Dari situ akan dikaji nilai-nilai seperti apa yang dihasilkan atau dibentuk media dalam menampilkan al-Qur’an. Hasil penelitian menunjukkan bahwa sekalipun terdapat upaya untuk menginformasikan ajaran- ajaran atau nilai-nilai yang terkandung dalam agama melalui media, tetapi hal itu masih dalam cakupan yang sempit. Uraiannya menunjukkan bahwa memang isi tulisan rubrik Hikmah ini lebih berorientasi pada ‘motivasi religius’ ketimbang analisis-filosofis.]